Revealing the consequences of male-biased trophy hunting on the maintenance of genetic variation - Rodríguez Muñoz, Rolando (2015)
Demographic models accounting for operational sex ratio (OSR) show that male numbers can have a substantial influence on the dynamics of wild populations. We used the Cantabrian capercaillie, a forest bird, as a model to assess the effects of the reduction in the number of breeding males (increased OSR) associated to male-biased hunting, on the genetics of the population. We based our assessment in the comparison of the dynamics of neutral markers transmitted by both parents (microsatellites) versus markers transmitted only by females (mitochondrial DNA—mtDNA). Parallel to the analysis of field data, we ran computer simulations to explore how different levels of OSR and two other important demographic factors, population size and connectivity, might influence the dynamics of genetic variation of microsatellites and mtDNA. We found evidence of a genetic bottleneck and low genetic variability affecting microsatellites but not mtDNA early in our study period, when male-biased hunting was more intense. This was followed by a decline in mtDNA variation around 10–20 years later. Simulations suggested that changes in genetic variation associated with high OSR had the closest similarity to those observed at the beginning of our study, whereas a combination of reduced size and migration rate better resembled the patterns found later on. Our findings indicate that male-biased hunting might have triggered the ongoing decline of the Cantabrian capercaillie, on its own or in combination with habitat configuration, and support the need to incorporate OSR into decision making for the management and conservation of exploited populations.